A STUDY ON THE RELATIONSHIP BETWEEN RELIGIOUS CONSUMERIST LANDSCAPE RESOURCES AND RELIGIOUS EXPERIENCE - Shen, C; Yu Liu, Shang (PEOPLE: International Journal of Social Sciences, 2015)
Faith in a Gods or divinities has always been the focus and sustenance of the development of civilizations, and is closely related to people’s lives. Coupled with the arts and humanities, astronomy, geography and customs, and living customs has played a part in shaping unique landscape resources and the possession of rich and deep cultural assets. With their involvement in religious activities, people have acquired sustenance and a sense of belonging from their religious beliefs and this has subsequently brought pleasure from tourism. There are over 12,000 registered temples in Taiwan, forming a special phenomenon in Taiwanese folk religion. Therefore, an important topic for discussion regarding to the development of religious tourism will be: how to shape landscape resources for religious consumerists in order to offer the consumerists profound experience, as well as creating an in-depth understanding of Taiwanese religious cultures and generating a reliance on recognition and emotions of consumerists. Themed on researches which were previously undertaken on the relationship between religious consumerist landscape resources and religious experience, this study adopts the Nankunshen Temple as the research object for empirical study. The research results of this study consist of: (1) through factor analysis, this study extracted the factor dimensions of religious consumerist landscape resources. In order, these dimensions are “the holiness and solemnity of the religion”,“the beauty of the magnificent art”, “atmosphere of the religious culture”, “the center of spiritual sustenance”” and “the reliance of living philosophy”. The factor dimensions of experience are “sensory experience”, “thought experience”, “emotional experience”, “action experience”, and “relational experience”. (2) In terms of the dimensions of the landscape resources of religious tourism, “the holiness and solemnity of the religion” was placed first, followed by “the beauty of magnificent art”; (3) In terms of the experience dimensions, the first place went to “sensory experience”, followed by “thought experience”. (4) After regression analysis, it is found that religious consumerist landscape resources were the most important factor for experience. In terms of sensory experience, the beauty of magnificent buildings occupied first place, followed by spiritual sustenance. In terms of emotional experience, the first place went to the center of spiritual sustenance, followed by the reliance of life philosophy. Regarding thought experiences, religious cultural atmosphere was in first place, followed by the center of spiritual sustenance. For the action experience, the first place was given to the center of spiritual sustenance, followed by religious cultural atmosphere. For relational experience, the reliance of life philosophy was in first place, followed by religious cultural atmosphere. The research results of this study can offer a reference for relevant organizations involved in the development of religious tourism.